PENALIZING MINORS WITHIN THE FRAMEWORK OF THE INTERNATIONAL HUMAN RIGHTS PROTECTION STANDARDS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
In the legal system of the Republic of Serbia, the Act on Juvenile Criminal Offenders and Protection of Minors in Criminal Law366 (hereinafter: the Juvenile Offenders’ Act), fully regulates the criminal law status of juvenile delinquents. Thus, autonomous juvenile criminal law was established as an instrument for protecting the society from juvenile delinquency, but also as a set of rules on the criminal law protection of juveniles. Although the Juvenile Offenders’ Act envisages diversion measures, the judiciary’s reaction to juvenile delinquency most frequently entails educational measures, but there is also an exceptional possibility of punishing juvenile offenders. International law standards pertaining to the rights of children and minors mandate a restrictive approach to punishing juvenile offenders. Therefore, this paper will look at the conformity of the normative framework of juvenile prison in Serbian law with the guidelines provided in the international catalog of juvenile rights.
Keywords: minors, prison, punishment, standards, measures